Painting with synesthesia translating auditory memory with abstract expressionism - Prado, Gabrielle Marie C.
This thesis was centered on the artist's personal experiences with sound and synesthesia. This discovery informed this work and was documented through the different stages of the artist's life, not as one burdened by these conditions, but as one inspired and informed by it.